2012
DOI: 10.1111/j.1365-2893.2012.01600.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial: efficacy and safety of telbivudine and lamivudine in treatment‐naïve patients with HBV‐related decompensated cirrhosis

Abstract: Patients with decompensated cirrhosis owing to chronic hepatitis B viral (HBV) infection have a high morbidity/mortality rate, and the treatment remains a challenge. We studied the safety and efficacy of telbivudine and lamivudine in such patients. This noninferiority, double-blind trial randomized 232 treatment-naive patients with decompensated HBV (1:1) in 80 academic hospitals to receive once-daily telbivudine 600 mg or lamivudine 100 mg for 104 weeks. Primary composite endpoint was proportion of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 34 publications
4
89
1
4
Order By: Relevance
“…Chan and associates suggested that telbivudine could increase blood flow to improve tubular dysfunction. 15 McKeage and team proposed another mech anism of renal protection of telbivudine excretion through passive diffusion, which would not result in mitochondrial DNA depletion or toxic effects on function of renal tubule cells. 16 Liang and associates showed that downstream effects by telbivudine decreased serum angiotensin-converting enzyme levels to inhibit the renin-angiotensin aldosterone regulatory system, with eGFR significantly increasing after long-term telbivudine treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Chan and associates suggested that telbivudine could increase blood flow to improve tubular dysfunction. 15 McKeage and team proposed another mech anism of renal protection of telbivudine excretion through passive diffusion, which would not result in mitochondrial DNA depletion or toxic effects on function of renal tubule cells. 16 Liang and associates showed that downstream effects by telbivudine decreased serum angiotensin-converting enzyme levels to inhibit the renin-angiotensin aldosterone regulatory system, with eGFR significantly increasing after long-term telbivudine treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, patients with baseline eGFRs from 60 to 89 mL/min/1.73 m 2 , older than 50 years, and with liver fibrosis/cirrhosis achieved an eGFR improvement of 17.2%, 11.4%, and 7.2%, respectively (66). In decompensated patients with a high renal risk, eGFR declined during LAM treatment (−4.6%), whereas it improved in LtD-treated patients (+2.0%; p=0.023) (67).…”
Section: Telbivudine and Renal Functionmentioning
confidence: 99%
“…Besides, LtD in comparison with other NAs showed a potential renal protective effect. In a double-blind randomized trial involving 232 treatment-naïve patients with decompensated CHB, LtD treatment was associated with a significant improvement in estimated glomerular filtration rate (eGFR) compared to LAM after 52 weeks of treatment (67). More importantly, Gane et al (66) gathered data of CHB patients who participated in the GLOBE trial for 2 years and in the long-term extension studies (4-6 years) as well as patients with decompensated cirrhosis (A2303 trial; a 2-year study) to assess renal function in CHB patients receiving LtD treatment.…”
Section: Telbivudine and Renal Functionmentioning
confidence: 99%
“…No cases of renal insufficiency are, on the contrary, reported with LAM. Moreover, renal function improvement (expressed as an increase in estimated glomerular filtration rate from baseline) was significantly greater in patients treated with LdT with respect to patients on LAM therapy (3.3 ± 3.3 mL vs 4.3 ± 3.1 mL, P = 0.02), according to a prospective randomised controlled trial on LdT and LAM [45] . The frequency of renal insufficiency at 1-year after starting antiviral treatment was reportedly similar between ETVand TDF-treated patients (5% vs 9%, P = 0.53) in a different study [44] .…”
Section: Antiviral Therapy and Decompensated Liver Diseasementioning
confidence: 99%